2014
DOI: 10.1155/2014/383910
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Percentage Prediction Using Intelligent Hybrid Approaches

Abstract: Excess of body fat often leads to obesity. Obesity is typically associated with serious medical diseases, such as cancer, heart disease, and diabetes. Accordingly, knowing the body fat is an extremely important issue since it affects everyone's health. Although there are several ways to measure the body fat percentage (BFP), the accurate methods are often associated with hassle and/or high costs. Traditional single-stage approaches may use certain body measurements or explanatory variables to predict the BFP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
0
18
0
5
Order By: Relevance
“…The literature study revealed that attempted ANN approaches to predict BF% in adults showed partly contradictory results. [15][16][17][18] Barbosa et al evaluated the data of 79 adults. 15 was not convincingly better than linear regression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature study revealed that attempted ANN approaches to predict BF% in adults showed partly contradictory results. [15][16][17][18] Barbosa et al evaluated the data of 79 adults. 15 was not convincingly better than linear regression.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recently, some attempts to involve an artificial neural network (ANN) approach to predict BF% in adults have been reported. [15][16][17][18] Artificial intelligence has also been successfully used to predict childhood obesity after age two, using data collected prior to the second birthday by a clinical decision support system. 19 ANN approaches are commonly used to address complex, linear, and nonlinear relations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research indicates that hybrid systems which are integrated with several standard ones can help to achieve a better performance for some applications. For example, the hybrid modeling applications have been reported in forecasting [57][58][59][60][61][62], credit risk [61], and manufacturing process [41][42][43][44]. As a consequence, this study proposes a two-step hybrid data mining mechanisms to predict the demand of ICO in Taiwan.…”
Section: Hybrid Modelsmentioning
confidence: 99%
“…Due to their greater generalization ability and superior performance in practical applications [23][24][25][26][27][28][29], this study uses artificial neural network (ANN) and support vector machine (SVM) to serve as the classifiers to identify three commonly observed disturbance patterns [20,30,31]. Those three process disturbance patterns include shift, trend, and cycle patterns.…”
Section: Introductionmentioning
confidence: 99%